Analysis of Factors Affecting Capital Structure on Listed Companies in Indonesia Stock Exchange 2017-2019 Period - Della Ayu Sevira; Muhammad Azhari (Almana : Jurnal Manajemen dan Bisnis, 2021)
Achieve the objectives of companies requires financial decisions that include capital structure. Capital structures in food and beverage companies are relatively low, so it doesn't necessarily make capital structures optimal. This research is conducted to examine factors that influence the capital structure of food and beverage companies listed on the Indonesia Stock Exchange in the 2017-2019 periods. The purpose of this research is to test both simultaneously and partially the influence of profitability, tangibility, firm size, sales growth, asset growth, business risk, firm activity, and liquidity on the capital structure. 14 of 26 companies have been selected as research samples from food and beverage companies listed in Indonesia Stock Exchange in 2017-2019, so 42 observations have been obtained. The method of analysis that using in this research is the multiple regressions analysis technique. This research shows that simultaneously profitability, tangibility, firm size, sales growth, asset growth, business risk, firm activity, and liquidity have a significant influence on the capital structure. The result of partial research shows that firm size and liquidity significantly influence the capital structure. Meanwhile, profitability, tangibility, sales growth, asset growth, business risk, and firm activity have no significant influence on the capital structure.